2019
DOI: 10.1177/0363546519854760
|View full text |Cite
|
Sign up to set email alerts
|

Substantial Biomechanical Improvement by Extracorporeal Shockwave Therapy After Surgical Repair of Rodent Chronic Rotator Cuff Tears

Abstract: Background: Characteristics of chronic rotator cuff tears include continuous loss of tendon structure as well as tendon elasticity, followed by a high failure rate after surgical reconstruction. Several studies have already shown the beneficial effect of extracorporeal shockwave therapy (ESWT) on tissue regeneration in tendon pathologies. Hypothesis: ESWT improves biomechanical tendon properties as well as functional shoulder outcomes in chronic rotator cuff reconstruction in rodents. Study Design: Controlled … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(24 citation statements)
references
References 46 publications
0
24
0
Order By: Relevance
“… 23 , 24 ESW treatment potentiates soft tissue regeneration. 25 - 27 Studies have shown that ESW treatment activates proliferation, migration, and gene expression in different cells. 28 - 31 ESW has been proposed as a non-invasive treatment that potentiates graft healing after ACL reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%
“… 23 , 24 ESW treatment potentiates soft tissue regeneration. 25 - 27 Studies have shown that ESW treatment activates proliferation, migration, and gene expression in different cells. 28 - 31 ESW has been proposed as a non-invasive treatment that potentiates graft healing after ACL reconstruction surgery.…”
Section: Introductionmentioning
confidence: 99%
“…Most rat studies involving rotator cuff healing have a limitation that there is no baseline data for the intact tendon-to-bone junction. 6,15,25,31,32…”
Section: Discussionmentioning
confidence: 99%
“…To ensure a proper fixation of tendon tissue, the Prolene suture was left in situ and used for RC reconstruction later. 19 The deltoid muscle was readapted and wound closure was performed with a No. 5.0 Vicryl suture (Ethicon).…”
Section: Methodsmentioning
confidence: 99%
“…The distal part of the humerus was then potted in polymethyl methacrylate. 19 Biomechanical testing was performed at room temperature. The SSP tendon was gripped in a specially designed sandpaper clamp at direct proximity of the insertion site of the tendon.…”
Section: Methodsmentioning
confidence: 99%